2006
DOI: 10.1518/001872006777724426
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Retention of Associations Between Auditory Icons and Denotative Referents: Implications for the Design of Auditory Warnings

Abstract: The practical implication of this study is that auditory icons having either direct or strong, indirect associations with warning events should be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…The potential use of VAS displays to help humans maintain spatial awareness was a primary motivator for this study, as the ability of operators to keep track of the locations of multiple sources of sound will need to be known for VAS displays to be effective for this purpose. Our use in this study of readily identified, environmental sounds ensured that target sounds could be nominated without ambiguity and is consistent with the proposed incorporation of such sounds in potential VAS-display applications (e.g., Stephan et al, 2006).…”
Section: Introductionsupporting
confidence: 76%
“…The potential use of VAS displays to help humans maintain spatial awareness was a primary motivator for this study, as the ability of operators to keep track of the locations of multiple sources of sound will need to be known for VAS displays to be effective for this purpose. Our use in this study of readily identified, environmental sounds ensured that target sounds could be nominated without ambiguity and is consistent with the proposed incorporation of such sounds in potential VAS-display applications (e.g., Stephan et al, 2006).…”
Section: Introductionsupporting
confidence: 76%
“…This is achieved by the alarm sound being a metaphor for the function it is describing. 'Good' metaphors (an interesting question of itself) can lead to very quick recognition needing only one or two exposures to the sound (Belz et al, 1999;Edworthy, Page et al, 2014;Graham, 1999;Leung et al 1997;Perry, Stevens et al 2007;Stephan et al, 2006;Ulfvengren, 2003). One of our goals in designing prototype sets of alarm sounds is to move on from small-scale tweaking of tonal alarm sounds (and consequently small-scale tweaking of the standard) which generally achieve only small improvements, to sets of alarm sounds which can be learned after very brief exposure.…”
Section: Introductionmentioning
confidence: 99%
“…They however noted, that usage of cell phone or other linguistic activities that happen during driving reduce the usefulness of verbal warning signals. Previous studies indicate auditory icons with solid connections to their referents initiate quick accurate reactions than abstract arbitrary sounds in laboratory research settings (Keller & Stevens, 2004;McKeown & Isherwood, 2007;Perry, Stevens, Wiggins, & Howell, 2007;Stephan, Smith, Martin, Parker, & McAnally, 2006).…”
Section: Introductionmentioning
confidence: 99%